Revisiting Impurity in Republican China: An Evaluation of the Modern Rediscovery of Bujing guan 不淨觀 - Ester Bianchi (Religions, 2021)
During the era of the Republic of China, a number of Buddhists rediscovered early meditation techniques. These practices were mainly revived from canonical scriptures, following a modern text-based approach to Buddhism. Within this framework, specific attention was devoted to the ‘visualization of the impure’ (bujing guan 不淨觀, Sk. aśubhabhāvanā), particularly in the form of the visualization of one’s own body transforming into a putrefying corpse and skeleton. Masters with various backgrounds (Modernist Buddhists, Yogācāra scholars, Tiantai 天台 and tantric masters) wrote articles and guides on this practice, which had the advantage of being common to both Hīnayāna/Śrāvakayāna and Mahāyāna. This study considers a selection of modern texts on bujing guan in an attempt to uncover why the meditation on impurity was favored and how it was revived.